Realistic Mathematics Education in Indonesia and Recommendations for Future Implementation: A Meta-Analysis Study - Tamur, Maximus; Juandi, Dadang; Adem, Angela Merici G. (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
This meta-analysis study aims to investigate the effectiveness of applying realistic mathematics education (RME) in Indonesia to students' mathematical abilities. This study analyzes 95 effect sizes from 72 studies that have been published in national and international journals or proceedings from 2010 to 2019. Comprehensive Meta-Analysis (CMA) software is used to aid analysis. As a result of the study, the overall effect size was 1.104, with a standard error of 0.065 according to the random-effects model. These results indicate that the average person who is ranked 13th in the experimental group is equivalent to those who are ranked 4th in the control group. This research was carried out by considering four characteristics, resulting in significant differences in terms of sample size and duration of treatment. Thus the application of RME in Indonesia is very effective in improving students' mathematical abilities by considering the sample size and duration of treatment.